1987
DOI: 10.1017/s0950268800062129
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic sensitivity and mutation rates to antibiotic resistance inMycoplasma mycoidesssp.mycoides

Abstract: SUMMARYThe antibiotic resistance ofMycoplasma mycoidesssp.mycoidesstrain T1was investigated. This strain was resistant to high levels ( > 100 μg ml−1) of rifampicin and nalidixic acid. It was sensitive to streptomycin, spectinomycin and novobiocin; however, single step mutants with high levels of resistance ( > 100 μg ml−1) were readily isolated. With erythromycin and tylosin for which the minimum inhibitory concentration (MIC) for the parent strain was < 0·1 μg ml−1, mutants resistant to > 100 μg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
2
7
0
1
Order By: Relevance
“…It is possible that further passages might have increased the resistance but this is considered unlikely in the light of other workers' results. Similar results were obtained by Hannan et al (1997) with M. hyopneumoniae and by Lee et al (1987) with M. mycoides. Osborn et al (1960) reported that strains less sensitive to tetracycline appeared only after prolonged treatment (5 months) of chickens with a very high dosage in the feed (1000 g/ton).…”
Section: Discussionsupporting
confidence: 86%
“…It is possible that further passages might have increased the resistance but this is considered unlikely in the light of other workers' results. Similar results were obtained by Hannan et al (1997) with M. hyopneumoniae and by Lee et al (1987) with M. mycoides. Osborn et al (1960) reported that strains less sensitive to tetracycline appeared only after prolonged treatment (5 months) of chickens with a very high dosage in the feed (1000 g/ton).…”
Section: Discussionsupporting
confidence: 86%
“…Finally, whole-genome sequencing revealed only one new mutation in the genomes of these transplants relative to the genome sequence determined with a population of cells before cloning and genome transfer into yeast. This frequency is consistent with the mutation rate of Mycoplasma 20 . Therefore, it is likely that no mutation in these genomes is attributed to our transfer procedure ( Supplementary Note 1 ).…”
supporting
confidence: 87%
“…In bacteria, mutation rate has been estimated for decades in vitro by detecting phenotypic traits that depend on SNPs, such as antibiotic resistance. The in vitro mutation rate for mycoplasmas is similar to that of other bacteria [33]. This finding is surprising since mycoplasmas lack the methylation-mediated DNA repair system commonly found in other bacteria whose genome has not been drastically reduced in size.…”
Section: Resultsmentioning
confidence: 75%